2017
DOI: 10.1186/s12889-017-4846-y
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to the implementation of a school-based physical activity policy in Canada: application of the theoretical domains framework

Abstract: BackgroundIn British Columbia Canada, a Daily Physical Activity (DPA) policy was mandated that requires elementary school teachers to provide students with opportunities to achieve 30 min of physical activity during the school day. However, the implementation of school-based physical activity policies is influenced by many factors. A theoretical examination of the factors that impede and enhance teachers’ implementation of physical activity policies is necessary in order to develop strategies to improve policy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 47 publications
3
51
0
1
Order By: Relevance
“…For example, Olstad et al [ 43 ] reviewed DPA policies across Canada; they reported that Ontario had a moderately strong policy; Alberta and British Columbia had weak policies; and Manitoba, Nova Scotia, and Prince Edward Island did not have official DPA policies. Variations in provincial policies related to school-based PA, paired with the fact that DPA implementation [ 44 ] and PE curriculum delivery policies seem to be inconsistent across the country, suggest that school board level policies and school practices contribute to teacher practices, regardless of training.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Olstad et al [ 43 ] reviewed DPA policies across Canada; they reported that Ontario had a moderately strong policy; Alberta and British Columbia had weak policies; and Manitoba, Nova Scotia, and Prince Edward Island did not have official DPA policies. Variations in provincial policies related to school-based PA, paired with the fact that DPA implementation [ 44 ] and PE curriculum delivery policies seem to be inconsistent across the country, suggest that school board level policies and school practices contribute to teacher practices, regardless of training.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the issues already highlighted, the research findings need to be placed in the context of both the strengths and limitations of the study. First and foremost, this was a pragmatic trial where a school district invested in an intervention model that reduced the barriers that are consistently identified as a hindrance to the development of teacher knowledge in PE, namely time and lack of opportunity [5,58]. Conversely, school district, health and recreation stakeholders leveraged health promotion funding to support the initiative.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has suggested that when teachers see the positive attributes and outcomes of PA they adopt their own strategies which help movement and PA to be truly integrated into classroom life [58]. Integration is particularly important due to the well reported time constraints within schools [20]. Time in relation to the ABs was talked about positively by participating teachers, stating that the overall implementation and transitions to learning afterwards were quick.…”
Section: Discussionmentioning
confidence: 99%
“…The increasing demands placed upon teachers and school staff to cover curriculum content and achieve academic targets should be considered alongside the feasibility and acceptability aspects. Teachers recognize the benefits of PA in improving learning, but they have reported lack of time as the key barrier to implementing daily PA [20,21]. School-based PA interventions need to be effective at increasing PA levels, but they also need to be feasible for teachers to implement within a time constrained school day.…”
Section: Introductionmentioning
confidence: 99%